Renal Pseudoaneurysms after Flexible Ureteroscopy and Holmium Laser Lithotripsy: A Case Report - Deng, Xin-xi; Zhang, Wensheng; Fu, Delai; Fu, Bin (Frontiers in Surgery, 2022)
Abstract Background: Flexible ureteroscopy (FURS) and holmium laser lithotripsy is considered one of the most minimally invasive and safe surgical methods for the treatment of renal calculi. Renal pseudoaneurysm is a rare complication after FURS holmium laser lithotripsy. We report a case of renal pseudoaneurysm after FURS and holmium laser lithotripsy and review the relevant literature to analyze the possible etiology and summarize the treatment. Case presentation: A 29-year-old male with a 2-year history of diabetes was admitted to the hospital because of right back pain for 5 days. A doppler ultrasound demonstrated bilateral renal calculi with bilateral mild hydronephrosis. The patient underwent one-stage right FURS and holmium laser lithotripsy and bilateral ureteral stent implantation. The urine was clear on the second day after the operation, and he was discharged from the hospital. Due to severe gross hematuria, he had to be hospitalized 28 days after the operation. A CT scan showed multiple blood clots in the right renal pelvis and bladder. An emergency blood transfusion and removal of the bladder blood clots and bilateral double J tubes were performed. His urine was clear for one week, and he was discharged from the hospital. He was hospitalized again 47 days after the operation because of fever and hematuria. A CT scan demonstrated blood clots in the bladder and right renal pelvis. Angiography showed a pseudoaneurysm in a small branch of the right renal artery, and hematuria stopped after selective renal artery embolization with microcoils. Conclusion: FURS and holmium laser lithotripsy is safe, but we should be aware of the possibility of renal artery pseudoaneurysms (RAP). Through careful operation during the surgery, avoiding kidney injury, reducing intrarenal pressure and controlling the time of operation may prevent the occurrence of this complication. Vascular embolization is the first choice for the treatment of pseudoaneurysms.